Adding whey and fishmeal to swine finishing diets - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1981)
One hundred fifty finishing pigs were studied to evaluate the effect of adding whey and/or fishmeal to a sorghum grain-soybean meal basal swine diet. No significant effects due to treatment were observed on rate of gain, daily feed intake, or feed per lb. of gain for finishing pigs.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Whey; Fishmeal; Finishing diets